Perencanaan Lanskap Agroedutourism di UPT. Sentra Ternak Sobangan, Kecamatan Mengwi, Kabupaten Badung - Zulfa, Zakiyatul; Sugianthara, Anak Agung Gede; Suardi, I Dewa Putu Oka (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022, 2022)
Agroedutourism Landscape Planning at Sobangan Livestock Center Technical Implementation Unit, Mengwi, Badung. Bali is one of the islands in Indonesia which has natural potential that can be developed as an attraction for tourism. One of them is agroedutourism. Sobangan Livestock Center Technical Implementation Unit is the center of Balinese cattle breeding and education which is managed by the Department of Agriculture and Food of Badung Regency, which has potential land as a tourist attraction. The purpose of this research is to plan a landscape that can support the breeding process of Balinese cattle, education, and can be used as an agroedutourism.This study used a survey method with data collection techniques through observation and literature study . Literature study is applied to obtain the formulation of the concept of agroedutourism. Meanwhile the field survey was applied to determine constraints and potentials to support Landscape planning Sobangan Livestock Center. The results of this research are in the formsite plan of a farm environmental arrangementthat can support the activities of breeding, education and facilities agroedutourism by considering the comfort for livestock and for users on the site.